Estimation. Part II: Double porosity model - Macías, J (2017)
MIM 1D transport model was successfully applied to simulate the asymmetric behavior observed in three breakthrough curves of tracer tests performed under natural gradient conditions in a phreatic fractured volcanic aquifer. The transport parameters obtained after adjustment with a computer program, suggest that only 50% of the total porosity effectively contributed to the advective-dispersive transport (mobile fraction) and the other 50% behaved as a temporary reservoir for the tracer (immobile fraction). The estimated values of hydraulic properties and MIM model parameters are within the range of values reported by other researchers. It was possible to establish a conceptual and numerical framework to explain the three-tracer tests curves behavior, despite the limitations in quality and quantity of available field information.